Association of MTHFR C677T Genotype With Ischemic Stroke Is Confined to Cerebral Small Vessel Disease Subtype. Issue 3 (March 2016) - Rutten-Jacobs, Loes C.A.; Traylor, Matthew; Adib-Samii, Poneh; Thijs, Vincent; Sudlow, Cathie; Rothwell, Peter M.; Boncoraglio, Giorgio; Dichgans, Martin; Meschia, James; Maguire, Jane; Levi, Christopher; Rost, Natalia S.; et al.
Abstract : Background and Purpose—: Elevated plasma homocysteine levels are associated with stroke. However, this might be a reflection of bias or confounding because trials have failed to demonstrate an effect from homocysteine lowering in stroke patients, although a possible benefit has been suggested in lacunar stroke. Genetic studies could potentially overcome these issues because genetic variants are inherited randomly and are fixed at conception. Therefore, we tested the homocysteine levels–associated genetic variant MTHFR C677T for association with magnetic resonance imaging–confirmed lacunar stroke and compared this with associations with large artery and cardioembolic stroke subtypes. Methods—: We included 1359 magnetic resonance imaging–confirmed lacunar stroke cases, 1824 large artery stroke cases, 1970 cardioembolic stroke cases, and 14 448 controls, all of European ancestry. Furthermore, we studied 3670 ischemic stroke patients in whom white matter hyperintensities volume was measured. We tested MTHFR C677T for association with stroke subtypes and white matter hyperintensities volume. Because of the established association of homocysteine with hypertension, we additionally stratified for hypertension status. Results—: MTHFR C677T was associated with lacunar stroke ( P =0.0003) and white matter hyperintensity volume ( P =0.04), but not with the other stroke subtypes. Stratifying the lacunar stroke cases for hypertension status confirmed this association in hypertensive individuals ( P =0.0002), but not in normotensive individuals ( P =0.30). Conclusions—: MTHFR C677T was associated with magnetic resonance imaging–confirmed lacunar stroke, but not large artery or cardioembolic stroke. The association may act through increased susceptibility to, or interaction with, high blood pressure. This heterogeneity of association might explain the lack of effect of lowering homocysteine in secondary prevention trials which included all strokes. Abstract : Supplemental Digital Content is available in the text.